Analisis Risiko Kesehatan Lingkungan Kandungan Nitrat pada Sungai Cisangkuy dan Ciwidey - Pramudita, Widya Rachma; Fathan, Fadhillah; Yuniarti, Arum Tri; Nurkarimah, Resa; Putri, Sonia; Sulistiyorini, Desi (Jurnal Kesehatan Lingkungan Mandiri, 2024)
Background: Clean water is a basic human need to fulfill daily life, such as drinking, cooking and sanitation needs. One of the important parameters in monitoring river water quality is nitrate. Increasing nitrate concentrations in river water can cause serious impacts, including the risk of water pollution and eutrophication which can harm river ecosystems. The purpose of this study is to analyze the risk level of nitrate in Cisangkuy and Ciwidey river water in Bandung City. Methods: This research utilizes secondary data and applies descriptive research methods. The data source comes from monitoring the water quality of the Cisangkuy and Ciwidey rivers in Bandung in February, June and October 2022, which was obtained from DLHK Prov. West Java, 2022. Data processing is carried out through risk analysis by calculating intake (ink). Results: The results of univariate analysis of the average nitrate content in Cisangkuy and Ciwidey River water amounted to 2.66 mg/l. While the results of the calculation of the risk level (Risk Quotient, RQ) is less than 1, this means that the nitrate content in the Cisangkuy and Ciwidey River water is not at risk for exposure in the next 30 years. Conclusion: The nitrate content in Cisangkuy and Ciwidey River water is not at risk for the next 30 years of exposure because the RQ value is less than 1.